Dependence of Sammon and Sequential Mapping Errors on Data - Montvilas, A. (Elektronika ir Elektrotechnika, 2009)
The Sammon nonlinear mapping along with the sequential nonlinear mapping has been investigated according their mapping errors dependence on data structure and on scatter of parameters of vectors in multidimensional space. A lot of experiments show that mapping error weakly depends on scattering of parameters but noticeably depends on configuration of data array. Examples are given. Ill 4, bibl. 9 (in English; summaries in English, Russian and Lithuanian).